Assess the financial performance indicators of commercial banks Comparative research of a sample of commercial banks and the Iraqi Arab Emirates For the period from 2004 2009 - abdulhussain jasim mohammad; Ahmed hussain (Iraqi Journal for Administrative Sciences, 2025)
 This research theme evaluation indicators of the financial performance of commercial banks which is one of the most important topics that show the actual performance of the banks, The This research evaluated the performance indicators Financial for a sample of commercial banks, Iraqi and United Arab Emirates and the comparison between the indicators of financial performance for the banking Baghdad and east, shrugged off the Iraqis, Dubai and Abu Dhabi, UAE nationals, and that this research has the importance of gaining it sheds light on the side by the difference between the assessment of financial performance of commercial banks from one country to another and shows the performance of any bank in terms of superior financial indicators from country to country, from one bank to another and research has reached some conclusions which include: • The research found that the performance of the banking Iraqi commercial banks for the period examined, the best performance of the bank to commercial banks UAE sample, because the Iraqi banks achieved (5) points for power (5) weaknesses of the UAE banks. • clear from the analysis of the banks separately (Baghdad, the Middle East, Dubai, Abu Dhabi) that the Bank of Baghdad achieved (4) strengths and Bank of the Middle East achieved (3) the strengths of either Bank of Dubai has achieved (1) point of strength and As for Bank of Abu Dhabi it did not achieve the strengths and, instead, low-achieving weaknesses negative hit (-7) and this shows that the Gulf banks affected by the repercussions of the global financial crisis that occurred in (2008) in contrast to commercial banks, Iraq, which was far from the effects and repercussions of the global financial crisis . In light of the conclusions of the research some of the recommendations including:  guide the commercial banks using modern and advanced methods in the performance of its business in order to reach better performance in line with developments in financial markets.  Identify the cause of poor performance of Bank of Iraq (Middle East) against the power of the performance of the commercial Bank of Baghdad and take advantage of the methods used for the bank to improve his performance.  When you stand on the reality of the performance of commercial banks in the UAE sample of the research must determine the cause of poor performance of Abu Dhabi Commercial Bank for the performance of the power of Dubai Commercial Bank and make use of the methods used for the bank to improve his performance.  A study with more expansion and the other performance indicators for the purpose of standing on the performance of commercial banks and evaluate their performance and to identify the causes of deterioration and weakness